Psycho-pedagogical factors of students' adaptation to educational activities in university - Gribok, Andrew (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
he article analyzes the theoretical bases of adaptation of students to study in higher education and the peculiarities of the process. Found that the process of adaptation of students to study inherent specific features, among them - the variety of behaviors that distinguished the claims of adulthood, particular sensitivity and vulnerability, increased arrogance, desire for clustering, volatility of interest and so on. Disclosed psychological and pedagogical conditions of adaptation and attempt to develop specific recommendations on the provision of first-year students help in adapting to the new conditions of life.
Keywords: adaptation; learning activities; psychological and pedagogical conditions; crises; external conditions; exclusion; diagnostics; training